Answer:
Brain and peripheral nerves
Step-by-step explanation: Idk i just guess
Well just plug those two numbers into the equation: 7(3) - 3(2) Which equals 15 so B) 15
A negative divided by a negative is a positive, so -14/-2 = 7
Hope this helped!
Answer:
-2
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
4(3+c)+c=c+4
(4)(3)+(4)(c)+c=c+4(Distribute)
12+4c+c=c+4
(4c+c)+(12)=c+4(Combine Like Terms)
5c+12=c+4
5c+12=c+4
Step 2: Subtract c from both sides.
5c+12−c=c+4−c
4c+12=4
Step 3: Subtract 12 from both sides.
4c+12−12=4−12
4c=−8
Step 4: Divide both sides by 4.
4c
4
=
−8
4
c=−2
Answer:
x = - 90
Step-by-step explanation:
Given
10x + 60 = 9x - 30 ( subtract 9x from both sides )
x + 60 = - 30 ( subtract 60 from both sides )
x = - 90